Digital competence in agile and hierarchical organizations : operational performance under global uncertainties - Adedoyin, Festus, 1989- (Routledge studies in innovation, organizations and technology, 2025)
This book explores the critical intersection of digital competence, operational performance, and organizational agility, offering insights for academics, professionals, and decision-makers navigating the digital era. Through a global lens, it examines digital transformation strategies across diverse contexts, including higher education, multinational organizations, and cultural landscapes, with a case study of Astana IT University for one of the chapters. The book delves into the implications of cybersecurity, data analytics, and business intelligence for enhancing digital competence, comparing agile and hierarchical organizational structures. It also addresses the challenges of uncertainty, the impact of cultural factors, and the opportunities presented by remote work and digital collaboration. Readers will gain practical frameworks and comparative analyses to strengthen digital transformation initiatives and improve organizational performance.This resource is invaluable for leaders seeking to foster agility, overcome uncertainty, and leverage technology for sustainable growth. It will be of interest to academics, professionals, and policymakers across a wide range of fields, including strategic management, technology and innovation management, and organizational behaviour.